A cognitive grammar study of anger words in Croatian: the interaction between metaphors and grammar - Stanojević, Mateusz-Milan; Ljubičić, Mateja (2012)
A cognitive grammar study of anger words in Croatian: the interaction between metaphors and grammar There are a variety of studies which deal with metaphorical expressions from a grammatical perspective. For instance, Stefanowitsch (Stefanowitsch 2004 ; Stefanowitsch 2006) has proposed a metaphorical pattern analysis (multi-word source domain expressions where a target domain lexical item has been inserted), as in the following Croatian example: (1) što je Ankaru odmah dovelo do erupcije ljutnje what is Ankara-acc immediately brought to eruption-gen anger-gen ‘which immediately led to an eruption of anger from Ankara’. In (1) the target domain expression ljutnje ‘anger’ has been inserted into the source domain expression dovelo do erupcije ‘led to an eruption’. It has also been shown that linguistic expressions may be grammatically different in metaphorical and non-metaphorical uses (Deignan 2005 ; Deignan 2006), which is to be expected because grammatical information may be used to tease out the various senses of polysemous items (Gries and Divjak 2009). In Croatian, which has a rich inflectional morphology, this is a relatively straightforward assumption. For example, in order to modify a noun by another noun, the genitive case of the modifying noun is required (erupcija-nom ljutnje-gen ‘an eruption of anger’). In this paper, we combine a metaphorical pattern analysis of the Croatian nouns ljutnja ‘anger’ and bijes ‘rage’ with a cognitive grammar analysis (Langacker 1987) of their metaphorical patterns based on data from the Croatian National Corpus. The aim is to show that conceptually closer grammatical relations (e.g. premodification, postmodification) result in fewer metaphors, which tend to be more central to the concept at issue, whereas conceptually distant relations (e.g. verb-object) produce more metaphors, which are less central (i.e. can appear with a variety of concepts). The results support the hypothesis, although relatively few metaphors were found. Based on the results we discuss the position of conceptual metaphor in the conceptualization of anger in Croatian. References Deignan, Alice. 2005. Metaphor and Corpus Linguistics. Converging evidence in language and communication research. Amsterdam, Philadelphia: John Benjamins. ———. 2006. The grammar of linguistic metaphors. In Corpus-Based Approaches to Metaphor and Metonymy, ed. Anatol Stefanowitsch and Stefan Thomas Gries, 106-122. Trends in linguistics. Studies and monographs 171. Berlin, New York: Mouton de Gruyter. Gries, Stefan Th., and Dagmar Divjak. 2009. Behavioral profiles: a corpus-based approach to cognitive semantic analysis. In New directions in cognitive linguistics, ed. Vyvyan Evans and Stéphanie Pourcel, 57-75. Amsterdam, Philadelphia: John Benjamins Publishing Company. Langacker, Ronald W. 1987. Foundations of Cognitive Grammar. Vol. 1: Theoretical Prerequisites. Stanford: Stanford University Press. Stefanowitsch, Anatol. 2004. Happiness in English and German: A metaphorical-pattern analysis. In Language, Culture, and Mind, ed. Michel Achard and Suzanne Kemmer, 137-149. Stanford: Center for the Study of Language and Information. ———. 2006. Words and their metaphors: A corpus-based approach. In Corpus-Based Approaches to Metaphor and Metonymy, ed. Anatol Stefanowitsch and Stefan Th. Gries, 63-105. Berlin, New York: Mouton de Gruyter.
Projekt MZOS
ENG